KESESUAIAN LATIHAN STORIES DUOLINGO DENGAN LATIHAN KETERAMPILAN MEMBACA SMA KELAS XII SEMESTER 1 - Muslimin, Annas; Julaikah, Dwi Imroatu (LATERNE, 2022)
Reading skills are one of the important skills in german learning. Proper practices are needed to support the development of learners' German language skills. The rapid development of technology helps educators to find new alternatives, including Duolingo which has interesting feature called stories. The 7th set of the stories feature contains several German practice questions about Hobbys to develop learner's reading skills in German. However, we have to make sure the compability of 7th set of the stories feature in Duolingo with the 2013 curriculum KD 3.2 and 4.2 for twelfth grade in the first semester for reading skills. This scientific article's purpose is to put into words the compability of the seventh set of the stories feature in Duolingo with KD 3.2 in 2013 Curriculum for twelfth grade in the first semester for reading skills. This scientific article is a descriptive qualitative article and use literature review as the method. This scientific article shows that the seventh set of the stories feature in Duolingo is compatible with the 2013 curriculum KD 3.2 and 4.2 for twelfth grade in the first semester for reading skills.